Effect of docosahexanoic acid (DHA) on quality of frozen-thawed bull semen using Tris extender - Kaka, Asmatullah; Haron, Abd Wahid; Yusoff, Rosnina; Degu, Nurhusien Yimer; Mada, Khumran Armiya'u; Behan, Atique Ahmed; Kaka, Ubedullah; Ebrahimi, Mahdi (2015)
This study was conducted to investigate the effect of DHA supplementation in Tris extender on frozen-thawed quality of bull sperms. Semen was collected by using an electro ejaculator. Ejaculates with acceptable quality were extended in Tris extender and divided into five groups to which 0 (control), 3, 5, 10, 15 ng/ml of DHA were added. The supplemented semen samples were sequentially incubated at 37°C for 15 minutes, cooled for 2 hours at 5°C, packaged into 0.25ml straws and cryopreserved in liquid nitrogen for 24 hours. Frozen-thawed semen evaluation resulted that significantly (P<0.05) higher values for all sperm parameters at 10ng/ml except DNA integrity which showed non-significantly (P>0.05) higher values at 10ng/ml. In conclusion, supplementation of Tris extender with DHA at 10ng/ml improves frozen-thawed quality of bull semen.